2012
DOI: 10.1037/a0027608
|View full text |Cite
|
Sign up to set email alerts
|

The differential effects of school tracking on psychometric intelligence: Do academic-track schools make students smarter?

Abstract: Prior research has shown that quantity of schooling affects the development of intelligence in childhood and adolescence. However, it is still debated whether other aspects of schooling-such as ability tracking or, more generally, school quality-can also influence intelligence. In this study, the authors analyzed intelligence gains in academic-and vocational-track schools in Germany, testing for differential effects of school quality (academic vs. vocational track) on psychometric intelligence. Longitudinal da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 123 publications
3
81
0
9
Order By: Relevance
“…A huge body of literature claims that tracking affects students' educational success and achievement as well as their emotional well-being (e.g., Oakes 1982;Baumert et al 2006;Ariga and Brunello 2007;Becker et al 2012). Similar to the differences between German states in regard to the transition regulations, there are considerable differences from state to state in the available range of school tracks in Germany (KMK 2014 ; compare for a description in detail KMK 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 96%
See 1 more Smart Citation
“…A huge body of literature claims that tracking affects students' educational success and achievement as well as their emotional well-being (e.g., Oakes 1982;Baumert et al 2006;Ariga and Brunello 2007;Becker et al 2012). Similar to the differences between German states in regard to the transition regulations, there are considerable differences from state to state in the available range of school tracks in Germany (KMK 2014 ; compare for a description in detail KMK 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…However, item format-as another item feature-has also been shown to be highly relevant in the context of DIF in reading tests (Rodriguez 2002;Lafontaine and Monseur 2009;Taylor and Lee 2012;Schwabe et al 2015). Regarding school tracking, literature discusses mainly three potential sources of differences in mean reading achievement, which might also relate to the emergence of specific strengths and weaknesses of students attending different tracks: (a) individual and social differences in students' preconditions at school entry (Luyten et al 2003), (b) institutional, and/or (c) compositional aspects of the different school tracks (e.g., Becker et al 2012). This study considers DIF caused by item format in reading test items for students in different school tracks following a Generalized Linear Mixed Models (GLMM) approach (De Boeck et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ritchie et al, 2012), and those that address effects of variation in the quality, not just the quantity, of education (e.g. Allensworth, Moore, Sartain, & de la Torre, 2015;Becker et al, 2012;Finn et al, 2014;Gustaffson, 2001) are all promising ways to progress toward clarifying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The general conclusion of such studies is that education improves general cognitive abilities: there is a clear relationship between years spent at school and level of cognitive abilities. a recent longitudinal study indicated that students taking academic tracks made greater gains than those receiving vocational education (Becker et al, 2012); furthermore, the results of a long-term longitudinal study suggest that the impact of education may be subject-specific rather than general (Ritchie, Bates and Deary, 2015). It was the problem solving assessment in the 2012 Programme for International Student assessment (PISa) which first provided data that demonstrated that there are large differences between educational systems in terms of improving a well-defined cognitive ability.…”
Section: Introductionmentioning
confidence: 99%